Modification of surface hardness, wear resistance and corrosion resistance of cold spray Al coated AZ31B Mg alloy using cold spray double layered Ta/Ti coating in 3.5 wt % NaCl solution. (November 2020) - Daroonparvar, M.; Khan, M.U. Farooq; Saadeh, Y.; Kay, C.M.; Kasar, A.K.; Kumar, P.; Esteves, L.; Misra, M.; Menezes, P.; Kalvala, P.R.; Bakhsheshi-Rad, H.R.; Gupta, R.K.
Highlights: Ti and Ta/Ti coatings noticeably reduced the wear rate of Al coated Mg alloy. Drawbacks associated with commercially pure Al coating mitigated with Ti top layer. Al layer compactness on Mg alloy was obviously raised in multilayered coating systems. A layer of Ta exceptionally improved the corrosion resistance of Ti/Al coated Mg alloy. No galvanic corrosion was seen at coatings / Mg alloy interface after immersion test. Abstract: In this research, cold sprayed Al coating layer on AZ31B Mg alloy was coated with cold sprayed Ti and Ta/Ti coatings, which noticeably reduced the wear rate of Al coated Mg alloy. Electrochemical corrosion tests and infinite focus 3D measurement results revealed that the high surface activity of commercially pure-Al coating, diffusion-controlled reactions, and formation of corrosion pits could be mitigated using Ti top coating. However, a dense layer of Ta on Ti coating exceptionally improved the corrosion resistance of Ti/Al coated AZ31B Mg alloy in neutral 3.5 wt.% NaCl solution This work gives a new strategy to considerably raise the wear and corrosion resistances of cold spray Al coated Mg alloys by double layered Ta/Ti coatings.